Intrauterina inseminacija (IUI) in večplodna nosečnost - Drobnič, Sašo (Zdravniški vestnik, 2003)
Background. Multiple pregnancies are relatively common complication of IUI following ovarian stimulation due to increased number of the preovulatory follicles in the procedure. We tried to estimate the influence of different stimulation protocols and other measures on the multiple pregnancy rates. Methods. Retrospective analysis of data from IUI cycles, influences of different stimulation protocols and patient preparing on multiple pregnancy rates and comparision of the results with those obtained from the literature. Results. Multiple pregnancy rate was 13% (24/183), which is, considering the overall pregnancy rate of 10.2% relatively low, but still ten times higher than in average population. Conclusions. Patient preparing and mild ovarian stimulation decrease multiple pregnancy rates in the IUI procedures. IUI can be changed to IVF-ET in high-risk cycles.
Keywords: Fertilization In Vitro; ginekologija; in vitro fertilization; Insemination, Artificial; maternica; Nosečnost večplodna; Oploditev in vitro; Oploditev umetna; ovulacija; porodništvo; Pregnancy, Multiple; večplodna nosečnost